2010
DOI: 10.1002/jcb.22705
|View full text |Cite
|
Sign up to set email alerts
|

Bone matrix proteins and extracellular acidification: Potential co‐regulators of osteoclast morphology

Abstract: Osteoclasts are signaled by the bone matrix proteins fibronectin (FN), vitronectin (VN), and osteopontin (OPN) via integrins. To perform their resorptive function, osteoclasts cycle between compact (polarized), spread (non-resorbing) and migratory morphologies. Here we investigate the effects of matrix proteins on osteoclast morphology and how those effects are mediated using RAW 264.7 cells differentiated into osteoclasts on FN, VN, and OPN-coated culture dishes. After 96 h, 80% of osteoclasts on FN were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…VN's effects on osteoclast activity were in line with its inhibitory effects on osteoclast differentiation in that it did not stimulate total resorption compared to FN or OPN and only slightly increased pit formation and resorbed area/osteoclast. The slight increase in pit formation and resorption per osteoclast correlates with our observation that VN increases the ratio of osteoclasts with a migratory morphology [Gramoun et al, 2010].…”
Section: Il-1b Was Measured By Elisa At 24 and 48 H (Bd) Each Data supporting
confidence: 71%
See 1 more Smart Citation
“…VN's effects on osteoclast activity were in line with its inhibitory effects on osteoclast differentiation in that it did not stimulate total resorption compared to FN or OPN and only slightly increased pit formation and resorbed area/osteoclast. The slight increase in pit formation and resorption per osteoclast correlates with our observation that VN increases the ratio of osteoclasts with a migratory morphology [Gramoun et al, 2010].…”
Section: Il-1b Was Measured By Elisa At 24 and 48 H (Bd) Each Data supporting
confidence: 71%
“…Another possible mechanism for increased osteoclast activation on FN involves extracellular pH regulation. Extracellular pH of osteoclasts on FN was indeed lower than cultures on TCP, VN, and OPN [Gramoun et al, 2010]. As low extracellular pH increases osteoclast resorption in vitro, the low pH resulting from FN offers plausible mechanism for the enhancement Fig.…”
Section: Il-1b Was Measured By Elisa At 24 and 48 H (Bd) Each Data mentioning
confidence: 93%
“…Interestingly, these effects were mimicked by RGD-containing peptides and blocked by an antibody directed against the ␣v␤3 integrin. Similarly, it was reported recently that osteoclast-like cells differentiated from murine RAW 264.7 cells on OPN were more spread than cells formed on vitronectin or fibronectin (39). On the other hand, Teti and co-workers (40) reported that authentic rabbit osteoclasts plated on an OPN-coated substratum exhibited less spreading than cells plated on a control surface.…”
Section: Discussionsupporting
confidence: 54%
“…Even in the presence of RANKL at a high concentration (100 ng/mL), monocytes on ECM still failed to differentiate toward functional osteoclasts, while RANKL at low concentrations, such as 25 ng/mL, was sufficient to induce BMMs to form multinucleated osteoclasts on standard TCPS. In a recent study, it was shown that ECM proteins (fibronectin, vitronectin, and osteopontin) modulated osteoclast morphologies between compact, spread, and migratory shapes, indicating that bone matrix proteins were essential for osteoclast resorption activity [29]. Kajahn et al .…”
Section: Discussionmentioning
confidence: 99%